Serum Calcium Levels in Chronic Kidney Disease Patient Stratified By Body Mass Index - Anthoni Anthoni; Rudi Supriyadi; Siti Nur Fatimah (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Most of the chronic kidney disease (CKD) patients have low blood calcium levels, yet hypercalcemia has a worse outcome in CKD patients. Interestingly, CKD patients with higher body mass index (BMI) have better outcomes. This study aimed to elucidate the difference in blood calcium levels stratified by BMI categories in patients with CKD.Methods: The study was conducted using a comparative analytical cross-sectional study design. Patients with CKD (n100), aged over 18 years old were included, Patients with the following were excluded: the history of hemodialysis, history of antioxidants, calcium and vitamin D supplement consumption, history of infection and malignancy. BMI of patients was categorized into underweight (<18.5 kg/m2), normal (8.5-22.9 kg/m2), and overweight or obese (≥23 kg/m2). Data were analyzed to compare blood calcium in different categories of BMI (Kruskal-Wallis test). Results: The age of patients with CKD included in this study had median age of 61 years old, predominantly was men (57%). The blood calcium level of CKD patients was on the lower border of the normal range. Median BMI was 23.48 kg/m2, of which 53% was categorized as overweight or obese. There was a trend that overweight/obese patients had higher blood calcium levels than underweight and normal-weight patients, however, no statistically significant difference between the BMI category (p=0.982).Conclusions: The blood calcium level in chronic kidney disease varies across the BMI category, however, no correlation with the BMI.